2008
DOI: 10.4103/0973-6247.39502
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ABO and Rh-D blood groups in the Benin area of Niger-Delta: Implication for regional blood transfusion

Abstract: ABO and Rhesus (Rh) blood group antigens are hereditary characters and are useful in population genetic studies, in resolving medico-legal issues and more importantly in compatibility test in blood transfusion practice. Data on frequency distribution of ABO and Rh-D in Niger-Delta region of Nigeria are not available; hence we made an attempt to retrospectively analyze the records on the blood donors, transfusion recipients and patients attending antenatal care or some other medical interventions. Over a twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
59
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 2 publications
15
59
3
Order By: Relevance
“…The prevailing blood group among the studied population showed that blood group O+ had the highest prevalence with 53.3%.This finding agrees with Enosolease and Bazuaye who reported 53.2% in Benin area of Niger-Delta, Abah and Joe-Cliff who reported that people in Blood group O were more than those of the other blood groups among blood donors in Port Harcourt and Odokuma et al who also reported blood group O as the most common among students of the Abraka campus of Delta State University in Nigeria [21,36,37]. This supports the universal knowledge that blood group O is the commonest of all the blood groups.…”
Section: Determination Of Blood Groupsupporting
confidence: 81%
“…The prevailing blood group among the studied population showed that blood group O+ had the highest prevalence with 53.3%.This finding agrees with Enosolease and Bazuaye who reported 53.2% in Benin area of Niger-Delta, Abah and Joe-Cliff who reported that people in Blood group O were more than those of the other blood groups among blood donors in Port Harcourt and Odokuma et al who also reported blood group O as the most common among students of the Abraka campus of Delta State University in Nigeria [21,36,37]. This supports the universal knowledge that blood group O is the commonest of all the blood groups.…”
Section: Determination Of Blood Groupsupporting
confidence: 81%
“…Blood group A, B, AB, and O had the 21.6%, 26.2%, 4.9% and 47.2% respectively. The result is similar to the result obtained by [5] [6].…”
Section: Resultssupporting
confidence: 81%
“…The results of this study showed that blood group O was the highest with a percentage frequency of 47.2% followed by blood group B with a percentage frequency of 26.2%, blood group A as 21.6% and AB as 4.9% which is in correlation with the study made by [9], but blood group A and B was found with variation in the frequency of distribution when compare with the study made in Nigeria as a whole by [6]. This could be as a result of variation in sample size.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…(13) 94.2% 5.79% Chittoor (14) 90.6% 8.42% Vellore (15) 94.5% 5.47% Shimoga-Malnad (16) 94.9% 5% Davangere (17) 94.8% 5.5% Eastern ahmedabad (18) 94.2% 5.8% Punjab (19) 97.3% 2.7% ( 24) 93.9% 6.1%…”
Section: Discussion:-mentioning
confidence: 99%